Stimulating Demand for AIDS Prevention Lessons from the RESPECT Trial - De Walque, Damien (The World Bank, 2012)
HIV-prevention strategies have yielded only limited success so far in slowing down the AIDS epidemic. This paper examines novel intervention strategies that use incentives to discourage risky sexual behaviors. Widely-adopted conditional cash transfer programs that offer payments conditioning on easily monitored behaviors, such as well-child health care visits, have shown positive impact on health outcomes. Similarly, contingency management approaches have successfully used outcome-based rewards to encourage behaviors that are not easily monitored, such as stopping drug abuse. These strategies have not been used in the sexual domain, so this paper assesses how incentives can be used to reduce risky sexual behavior. After discussing theoretical pathways, it discusses the use of sexual-behavior incentives in the Tanzanian RESPECT trial. There, participants who tested negative for sexually transmitted infections are eligible for outcome-based cash rewards. The trial was well-received in the communities, with high enrollment rates and more than 90 percent of participants viewing the incentives favorably. After one year, 57 percent of enrollees in the "low-value" reward arm stated that the cash rewards "very much" motivated sexual behavioral change, rising to 79 percent in the "high-value" reward arm. Despite its controversial nature, the authors argue for further testing of such incentive-based approaches to encouraging reductions in risky sexual behavior